Attempts on Increasing Life Prosperity of the Recipients Through Productive Zakat Program of LAZ Ummul Quro - Astuning Rini,; Ahmad Makhtum, (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
Productive zakat is zakat distributed to mustahiq that can be managed and developed, the property can be used as capital, and improve the economic status of mustahiq. In order to improve the welfare of mustahiq in Jombang Regency, this research analyses the Productive Zakat Program of Lembaga Amil Zakat Ummul Quro (LAZ-UQ). This research uses descriptive qualitative research. The data used is primary data. Primary data obtained from documentation, observation, and interviews. This study uses Miles and Huberman data analysis. Four main components are involved in data analysis: data collection, data reduction, data presentation, and conclusion drawing or verification. The results of the study showed that LAZUQ's productive zakat programme succeeded in having a significant impact on mustahik's welfare, improving mustahik's basic needs, and helping them achieve economic independence.